Economic Facts Of Sumatra And Kalimantan Islands For 10 Years - Boy Piter Nizu Kekry; Muhammad Fahmi (CV. Green Publisher Indonesia, 2021)
Background: The formulation of this scientific research problem is what are the scientific facts that can be obtained, for 10 years on the island of Sumatra and Kalimantan. Research purposes: The purpose of this study is identifying scientific facts the direction and pattern of economic growth that occurs on the islands of Sumatra and Kalimantan. Research methods: The researcher applied quantitative approach, along with descriptive quantitative techniques. Research results: The results of this research are, there are 2 patterns of economic growth on the islands of Sumatra and Kalimantan during these 10 years. The trend towards growth on these two islands is, has a fluctuating tendency and has indications of a downward trend over the past 10 years. Some special findings are: (1) Aceh Province is quite risky, because over the past 10 years has historical economic growth movements that form the depth of the valley (can be indicated recession), (2) East Kalimantan as many as 4 times over the last 10 years, experiencing negative economic growth, (3) The plantation sector, through CPO exports is able to have its own impact, on the economy of South Kalimantan in 2020. Specifically for economic growth in 2020, it is a special record because of the overall economic growth of 10 provinces on the island of Sumatra and 5 provinces on the island of Kalimantan with negative growth performance. Conclusion: For Sumatra Island there are 2 different forms of patterns between provinces, pattern 1: Aceh, Riau and Riau Islands. For the case of Aceh province is quite risky because for the past 10 years, it has historical economic growth movements that can indicate recession